Effect of a select menhaden fish meal in starter diets for pigs - Stoner, G.R.; Allee, G.L.; Johnston, M.E.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A growth study was conducted to evaluate the effect of a select menhaden fish meal (SMFM) as a protein source in starter diets for pigs. A total of 150, 3-week old weaned pigs were utilized. Diets were formulated by replacing soy protein with protein from SMFM. The replacement of soy protein with SMFM elicited a quadratic response in average daily gain (ADG) and average daily feed intake (ADFI) by the end of week 5. Inclusion of SMFM at 8% yielded the maximum observed ADG, whereas ADFI was maximized with the 12% SMFM diet. Addition of SMFM did not affect feed conversion. These results suggest that SMFM may have potential as a protein source in starter diets for the early weaned pig.
Keywords: Swine; Menhaden fish; Starter diets